Evaluation of The Local Village Assistance Program: Case Study of Budget Management in Bakas Traditional Village, Banjarangkan District, Klungkung Regency - Sumawidayani, Nyoman (Iapa Proceedings Conference, 2024)
The financial management of the Bakas Traditional Village, especially in the planning process and use of the Regional Revenue and Expenditure Budget (APB) of the Bakas Traditional Village, has been accompanied by the Village's Local Assistance Officer. Even though it has subsided, there are still irregularities in financial management in the Bakas Traditional Village, one of the cases currently occurring, namely the corruption case of the Traditional Village LPD. Based on these problems, it is necessary to evaluate the Local Village Assistance Program in Managing the Bakas Traditional Village Revenue and Expenditure Budget (APB). This research aims to evaluate the implementation of the Village Local Facilitator Program in Managing the Revenue and Expenditure Budget (APB) of the Bakas Traditional Village, as well as finding and formulating the work pattern of the Traditional Village Local Facilitator in Managing the Revenue and Expenditure Budget (APB) of the Bakas Traditional Village. The research method used in this research is a qualitative research method with a descriptive approach. The research results show that the Village Facilitator accompanies every process in the planning, implementation and accountability of the Traditional Village APB. The existence of a Traditional Village Assistant can help in managing the administration of the Bakas Traditional Village regarding planning the use of funds and the Sikuat reporting system.